2021
DOI: 10.1016/j.acra.2021.08.010
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of Imaging Studies in Olfactory Dysfunction Secondary to COVID-19

Abstract: Rationale and Objectives Hyposmia/anosmia is common among patients with COVID-19. Various imaging modalities have been used to assess olfactory dysfunction in COVID-19. In this systematic review, we sought to categorize and summarize the imaging data in COVID-19-induced anosmia. Material and Methods Eligible articles were included after a comprehensive review using online databases including Google scholar, Scopus, PubMed, Web of science and Elsevier. Duplicate results,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
38
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(41 citation statements)
references
References 38 publications
2
38
1
Order By: Relevance
“…Eliezer et al 16 found that OD and OC obstruction are present at the early stage of the disease, and improved both at one-month follow-up, suggesting that OD in Covid-19 patients was caused, at least in part, by reversible inflammatory changes in the OC. In a recent systematic review 17 , opacification of OC (60/218 - 27.5%) together with normal OB morphology and signal intensity (68/218 - 31.2%) were the most common imaging findings in patients with olfactory dysfunction secondary to COVID-19. In our study, we found only partial OC obstruction in only 4/11 patients on the initial MRI, totally regressive during follow-up, explaining only partly OD.…”
Section: Discussionmentioning
confidence: 99%
“…Eliezer et al 16 found that OD and OC obstruction are present at the early stage of the disease, and improved both at one-month follow-up, suggesting that OD in Covid-19 patients was caused, at least in part, by reversible inflammatory changes in the OC. In a recent systematic review 17 , opacification of OC (60/218 - 27.5%) together with normal OB morphology and signal intensity (68/218 - 31.2%) were the most common imaging findings in patients with olfactory dysfunction secondary to COVID-19. In our study, we found only partial OC obstruction in only 4/11 patients on the initial MRI, totally regressive during follow-up, explaining only partly OD.…”
Section: Discussionmentioning
confidence: 99%
“…In human studies, SARS-CoV-2 has been detected in the OB of autopsied cases 40,41 . Imaging studies have also shown hyperintensity of the OB on T2 uid-attenuated inversion recovery magnetic resonance images 15,42 and a pattern of hypometabolism involving the olfactory system (orbitofrontal cortex and olfactory and rectus gyri) on positron emission tomography of brain 43 . A study on rhesus monkeys reported that SARS-CoV-2 primarily invades the central nervous system via the OB 39 .…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the nasal and oral cavities are considered the major routes of SARS-CoV-2 infection. Although the mechanisms underlying olfactory dysfunction related to COVID-19 have been gradually elucidated through histological and genomic examinations 7,11−13 and imaging studies 14,15 , it remains di cult to disentangle the involved mechanisms because of the heterogeneity of presentations 16 . Currently, the following mechanisms are being considered: 1) transient conductive olfactory dysfunction resulting from airway blockage due to local in ammation and edema of the nasal mucosa in the olfactory cleft and nasal passages; 2) temporary sensorineural olfactory dysfunction due to damage to supporting tissues such as the sustentacular cells, Bowman's gland, and microvillar cells, excluding mature olfactory receptor cells (ORNs); 3) chronic or permanent sensorineural olfactory dysfunction due to damage to the ORNs; 4) central olfactory dysfunction due to SARS-CoV-2 infection of the olfactory bulb (OB) and olfactory cortex [16][17][18] .…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the nasal and oral cavities are considered to be the major routes of SARS-CoV-2 infection. Although the mechanisms underlying olfactory dysfunction related to COVID-19 have been gradually elucidated through histological and genomic examinations ( Singh et al., 2020 ; Butowt and von Bartheld, 2021 ; Sato et al., 2021 ; Ueha et al., 2021 ) and imaging studies ( Naeini et al., 2020 ; Keshavarz et al., 2021 ), it remains difficult to disentangle the involved mechanisms because of the heterogeneity of presentations ( Xydakis et al., 2021 ). Currently, the following mechanisms are being considered: 1) transient conductive olfactory dysfunction resulting from airway blockage due to local inflammation and edema of the nasal mucosa in the olfactory cleft and nasal passages; 2) temporary sensorineural olfactory dysfunction due to damage to supporting tissues such as the sustentacular cells, Bowman’s gland, and microvillar cells, excluding mature olfactory receptor cells (ORNs); 3) chronic or permanent sensorineural olfactory dysfunction due to damage to the ORNs; 4) central olfactory dysfunction due to SARS-CoV-2 infection of the olfactory bulb (OB) and olfactory cortex ( Xydakis et al., 2021 ; Ye et al., 2021 ; Zhang et al., 2021 ).…”
Section: Introductionmentioning
confidence: 99%